2009
DOI: 10.1148/radiol.2532082010
|View full text |Cite
|
Sign up to set email alerts
|

Radiologic and Nuclear Medicine Studies in the United States and Worldwide: Frequency, Radiation Dose, and Comparison with Other Radiation Sources—1950–2007

Abstract: The U.S. National Council on Radiation Protection and Measurements and United Nations Scientific Committee on Effects of Atomic Radiation each conducted respective assessments of all radiation sources in the United States and worldwide. The goal of this article is to summarize and combine the results of these two publicly available surveys and to compare the results with historical information. In the United States in 2006, about 377 million diagnostic and interventional radiologic examinations and 18 million … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
428
2
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 748 publications
(442 citation statements)
references
References 13 publications
6
428
2
6
Order By: Relevance
“…Due to the increase in life expectancy of the general population, spreading and increasing adherence to screening programs, and the effectiveness of medical and surgical therapies that increased the prevalence of oncological diseases, there has been an exponential increase in the number of radiological examinations performed for screening, diagnosis, and follow-up of diseases [1].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the increase in life expectancy of the general population, spreading and increasing adherence to screening programs, and the effectiveness of medical and surgical therapies that increased the prevalence of oncological diseases, there has been an exponential increase in the number of radiological examinations performed for screening, diagnosis, and follow-up of diseases [1].…”
Section: Introductionmentioning
confidence: 99%
“…Medical exposure to ionizing radiation from X-rays and in nuclear medicine is known to be the largest man made source of radiation exposure (Mettler et al, 2009). Such exposure is of considerable concern for interventional cardiologists due to increasing workloads and intricacy of procedures over the last decade (Cousins et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study performed by the National Lung Screening Trial (NLST) using computed tomography (CT) showed a 20 % reduction in death due to lung cancer mortality [4]. However, CT is controversial due to the higher radiation doses required, higher cost, and the large number of indeterminate nodules [5][6][7][8]. The speed of acquisition available with flat panel imaging technology has made biplane stereoscopic systems feasible.…”
Section: Introductionmentioning
confidence: 99%